2006
DOI: 10.1080/14639230600887866
|View full text |Cite
|
Sign up to set email alerts
|

Surfing the Net for medical information aboutpsychological trauma: An empirical study of thequality and accuracy of trauma-related websites

Abstract: Psychological trauma is a major public-health problem, and trauma victims frequently turn to the Internet for medical information related to trauma. The Internet has many advantages for trauma victims, including low cost, privacy, use of access, and reduced direct social interactions. However, there are no regulations on what is posted on the Internet, or by whom, and little is known about the quality of information currently available related to the topic of psychological trauma. The purpose of this study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 28 publications
1
35
0
2
Order By: Relevance
“…Bremner, Quinn, Quinn, & Veledar, 2006;Childs, 2005;Risk & Dzenowagis, 2001). In response to concerns about incomplete, misleading, inaccurate, or dangerous online mental and physical health information and practices, two major approaches have arisen in an attempt to guide developers/researchers of health websites and to assist consumers in identifying information resources of good quality.…”
Section: Existing Quality Standardsmentioning
confidence: 99%
“…Bremner, Quinn, Quinn, & Veledar, 2006;Childs, 2005;Risk & Dzenowagis, 2001). In response to concerns about incomplete, misleading, inaccurate, or dangerous online mental and physical health information and practices, two major approaches have arisen in an attempt to guide developers/researchers of health websites and to assist consumers in identifying information resources of good quality.…”
Section: Existing Quality Standardsmentioning
confidence: 99%
“…Substantial shortcomings were identified in the categories of technical criteria, design, readability, accuracy, and completeness. There is little evidence from more recent reviews of a range of medical conditions, such as cancer [5], osteoporosis [6], and allergic rhinitis [7], as well as mental health disorders such as depression [8][9][10][11], psychological trauma [12], and obsessive-compulsive disorder (OCD) [13•], that this situation is improving. Some of these websites may contain information that is actually detrimental to one's health.…”
Section: Introductionmentioning
confidence: 99%
“…However, research on Web interventions for trauma survivors has received little attention to date. The importance of critical evaluation of Web-based traumatic stress interventions was recently made abundantly clear by Bremner et al (2006), who reported that out of 80 identified sites targeting trauma survivors, 42% provided inaccurate or harmful information and only 18% of the sites provided any scientific references for the information provided. Almost half were not authored by mental health professionals at all.…”
Section: Web-based Interventions For Traumatic Stressmentioning
confidence: 99%